Cognitive impairment in patients with chronic noncommunicable diseases: a review - Assonov, Dmytro (Psychosomatic Medicine and General Practice, 2019)
The aim. This review aimed to summarize the information about the specific weight and the clinical significance of cognitive impairment in the course and prognosis of major chronic noncommunicable diseases. Materials and methods. Scientific literature from 2013 to 2018 on the cognitive impairment in patients with noncommunicable diseases was analyzed. Publications from previous years were taken into account in the absence of new research in this area or if conclusions have not lost relevance. Under the cognitive impairment dementia or mild cognitive impairment were understood. Results. Cognitive impairment is common for chronic cardiovascular diseases, both central nervous system and non-central nervous system cancer, chronic lung diseases, diabetes, and presented mostly from mild to moderate form. It can be caused by pathophysiological changes related to the underlying disease (in all diseases reviewed) or its treatment (in the case of cancer and diabetes), such as hypoxia, cerebral hypoperfusion, inflammation, acidosis, etc. Cognitive impairment can reduce adherence to medication, self-management, recovery from disability; impact different social and daylife activities, such as academic performance, employing, driving, reading and other life aspects. For central nervous system cancer, the cognitive decline also serves as an indicator of the tumor possible localization, a prognostic factor of survival and an indicator of the cancer recurrence. Conclusions. Cognitive impairment is highly prevalent in patients with all major types of chronic noncommunicable diseases, with the executive function, memory, and attention impaired most often. It reflects the severity of the underlying disease and its effect on the brain. Cognitive impairment can negatively affect the course, prognosis and treatment of major chronic noncommunicable diseases by reducing the management and self-management of therapy, adherence to therapy, quality of life, functional and social outcome and patient`s autonomy. Identification of cognitive impairment, development of the ways to treat or compensate it, minimization of the poor cognitive function negative impact on course and prognosis is important for successful chronic noncommunicable disease management.